Properties of AlNx thin films prepared by DC reactive magnetron sputtering - Stafiniak, Andrzej; Muszyńska, Donata; Szyszka, Adam; Paszkiewicz, Bogdan; Ptasiński, Konrad; Patela, Sergiusz; Paszkiewicz, Regina; Tłaczała, Marek (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
In this paper, the results of investigation of the influence of cathode current on optical and dielectric AlNx thin-film properties are presented. AlNx films were prepared by pulsed DC reactive magnetron sputtering of Al target on substrates at room temperature. For characterization of fabricated test structures C-V spectroscopy, ellipsometry measurement and atomic force microscopy (AFM) were used.
Optica Applicata, Vol. 39, 2009, nr 4, s. 717-722
Keywords: optyka; aluminum nitride (AlN); thin films; reactive magnetron sputtering; alternative dielectrics